MORPHO-AGRONOMIC AND GENETIC DIVERSITY AMONG TWELVE SICILIAN AGRO-ECOTYPES OF LENTIL (LENS CULINARIS) - P. Ruisi; M. Longo; F. Martinelli; G. Di Miceli; A. S. Frenda; S. Saia; F. Carimi; D. Giambalvo; G.Amato (Journal of Animal and Plant Sciences, 2015)
Although Sicily is relatively small (about 25000 km2), it accounts for several agro-ecotypes of lentil (Lens culinarisMedik.), for many of which no data on morphological, agronomic, and organoleptic characteristics are available to date. Thus, experiments were performed to characterize 12 lentil agro-ecotypes from different areas of Sicily, including some small islands surrounding the main island, and to assess the extent of genetic diversity (by means of six inter-simple sequence repeat [ISSR] primers). A famous agro-ecotype from central Italy (CastellucciodiNorcia) and two commercial varieties from Canada (Eston and Laird) were also included in the study. The results showed a large degree of genetic diversity (based on ISSR markers) and variability in pheno-morphological and agronomic traits. In contrast, the intra-accession variability was on average rather low. The agronomic (productivity, nitrogen fixation capacity) and qualitative (lipid content, hydration coefficient) attributes of several Sicilian agro-ecotypes were more pronounced than those of the controls. This fact certainly represents a prerequisite for their future economic valorization. Moreover, the observed variability may be of interest from the point of view of breeding.
Keywords: Phenotypic diversity; Molecular markers; ISSR; Hydration coefficient; Nitrogen fixation